Bis[3-ethyl-4-(4-methoxyphenyl)-5-(2-pyridyl)-4H-1,2,4-triazole-κ(2) N (1),N (5)]bis(perchlorato-κO)copper(II) acetonitrile disolvate - Huang, Liaocheng (International Union of Crystallography, 2008)
In the title compound, [Cu(ClO(4))(2)(C(16)H(16)N(4)O)(2)]·2CH(3)CN, the Cu(II) atom, located on an inversion center, is in a tetragonally distorted octahedral environment, coordinated by four N atoms of two bidentate 3-ethyl-4-(4-methoxyphenyl)-5-(2-pyridyl)-4H-1,2,4-triazole ligands in equatorial positions and by the O atoms of two perchlorate groups in axial positions. The long axial Cu—O bond of 2.4743 (17) Å is the result of the Jahn–Teller effect.